Kinetics and thermodynamics characteristics of cationic yellow X‐GL adsorption on attapulgite/rice hull‐based activated carbon nanocomposites. Issue 3 (28th July 2012) - Liu, Wenjie; Yao, Chao; Wang, Maohua; Ji, Junling; Ying, Lin; Fu, Chengyi
<x xml:space="preserve">Abstract</x> Attapulgite/activated carbon (ATP/AC) nanocomposites were prepared by the calcination of ATP and rice hull. ATP/AC nanocomposites were characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy analysis. The kinetic and thermodynamic parameters of the adsorption of cationic yellow X‐GL (CY) in aqueous solution on ATP/AC composites were studied. During all experiments, CY concentration was determined by UV–vis spectrophotometer. Research on the thermodynamic behavior indicated that the adsorption of CY obeyed the Langmuir isotherm model. The adsorption enthalpy was −16.37 kJ/mol, the Gibbs‐free energy was −28.73 to −27.04 kJ/mol, and the entropy was about 35 J mol−1 K−1, which showed that the adsorption process was both exothermic and spontaneous. The kinetic parameters showed that absorption of CY on ATP/AC composites was best described by pseudo‐second‐order kinetics. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 655–662, 2013